Some general results on restricted k-mean graph. (18th May 2020) - Gayathri, B.; Gopi, R
Abstract: A graph G = ( p, q ) is said to have a restricted k -mean labeling if there is an injective function f from the vertices of G to k – 1, k, k + 1, … , k + q – 1 such that when each edge uv is labeled with then the resulting edge labels k, k + 1, k + 2, … , k + q – 1 are all distinct where k is a positive integer greater than or equal to one. A graph that admits a restricted k -mean labeling is called a restricted k -mean graph.